Photolytic Behavior of Silver Iodide - Burley, G. (J Res Natl Bur Stand A Phys Chem, 1963)
Silver iodide exposed to high intensity radiation in the visible light spectrum was found to yield a powder X-ray diffraction pattern showing marked deviations from ideality. It was found possible to correlate these with a decrease in primary extinction, indicating a constant progress from an ideal to a mosaic type crystallinity. Large single crystals showed pronounced asterism in transmission Laue photographs under similar experimental conditions. Small amounts of colloidal silver were detected. A mechanism for this process in silver iodide is proposed, in general agreement with the theory of the photographic process. The primary difference from the other silver halides appears to be a considerably slower rate, permitting the observation of a two step process in detail.